ESENSI PAHAM KONSEP KONSTITUALISME DALAM KONTEKS PENYELENGGARAAN SISTEM KETATANEGARAAN - Bactiar . (Jurnal Surya Kencana Satu : Dinamika Masalah Hukum dan Keadilan, 2016)
Studies in this study is the notion Essence Constitutionalism in the Context of the Implementation of the constitutional system. Constitutionalism for modern states as an inevitability. In the idea of constitutionalism, the constitution is the embodiment of supreme law that must be obeyed by all parts of the country. This study uses normative juridical research. Philosophical meaning of this understanding, first, the power must be limited, Second, the implementation of the power held by general agreement that crystallized into the constitution, and Third, the exercise of power always requires accountability within the framework of the constitution . Keywords: Essence, Constitualism, Contitutional System